Effect of Multiple Piezoelectric Transducer on Fused Deposition Modeling to Improve Parts Surface Finish - Maidin, S.; Mohamed, A.S.; Mohamed, S.B.; Wong, J. H.U.; Sivarao, S. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
AM which embrace as a new range technology of creating and producing end user parts in term of adding material layer by layer to create solid objects from 3D CAD data. AM, in particular Fused Deposition Modeling (FDM) used (ABS) thermoplastic, have shown the most popular among the industry as its technology can print complex geometrical part without human intervention and tools. However, FDM fierce enemy, whereas the common problem of stair-stepping, which means that seam lines appear between layers and excess material if often left as a residue, cause to lead rough surface and poor quality finish. It is often desirable for an AM printed parts to have aesthetic and functional characteristic. Hence, reducing layer thickness will generally improve surface roughness, but will add to the build time for the model. As an interest to investigate the use of ultrasonic for FDM, this experiment will focus on the effect of applying multiple piezoelectric transducer on a FDM printer. This paper aims to explore the effect of using multiple piezoelectric with different frequency applied (27, 40, 50 kHz) to study the improvement made on the surface of the printed part. An ultrasonic transducer firmly attached onto the printer platform. Optical microscope with the aid of pro VIS software version 2.90 was used to measure the quality of surface roughness of samples printed with vibration in the above stated frequency. It was found that 1 piezo with 50 kHz frequency achieved an improved surface finish due to less layer thickness defect and finer layer thickness produce.